Contradictory Speech in the Dialogue of Teddy Soeraatmadja's Lovely Man Film - Siyam, Sahrul; Rustono, Rustono; Haryadi, Haryadi (Jurnal Sastra Indonesia, 2024)
This study examines the contradictory speech between the two main characters in the film "Lovely Man" through a pragmatic approach. The film tells the story of the relationship between a student and her father, who is a transvestite, showing differences in backgrounds and complex social conflicts. Through dialogue analysis, this study found that contradictory speech reflects social tensions, hidden feelings, gender identity issues, and social stigma. Contradictory speech not only serves as a means of communication but also as a reflection of the social and cultural background of its characters. This study uses a qualitative approach with a pragmatic analysis method to examine contradictory speech in the movie "Lovely Man." The data is taken from a fragment of dialogue between the two main characters, Cahaya and Ipuy, in the film. This study uses pragmatic matching methods and data analysis techniques in the form of observation and recording techniques. The methodological steps used in this study include data classification, analyzing data based on a theoretical framework, and drawing conclusions based on data analysis. This research provides in-depth insights into how social contexts affect verbal and non-verbal communication. This can benefit academics, communication practitioners, filmmakers, and the general public in understanding and managing complex social interactions.